Effect of Capital Structure on Profit of PT Telekomunikasi Indonesia Tbk - Dharmayanti, Shasy; Padandi, Yulpa; P, Futri Regina; Adwiah, Radiatul; Yunus, Muh. Haekal; Julyarman, Nasrun (ProBisnis : Jurnal Manajemen, 2024)
This study aims to analyze the effect of capital structure on profit at PT Telekomunikasi Indonesia Tbk. Capital structure is measured through the composition between own capital and loan capital. The data used in this study are the financial statements of PT Telekomunikasi Indonesia Tbk for three years, from 2020 to 2022. The research method used is simple linear regression analysis to determine the relationship between capital structure and company profits. The results showed that there were fluctuations in the components of own capital, loan capital, and profit level during the study period. In 2020, own capital amounted to 120,889 billion rupiah and loan capital amounted to 126,054 billion rupiah with a total profit of 29,563 billion rupiah. In 2021, own capital increased to 145,399 billion rupiah and loan capital increased to 131,785 billion rupiah with a profit of 33,948 billion rupiah. However, in 2022, own capital increased slightly to 149,262 billion rupiah, while loan capital decreased to 125,930 billion rupiah with a profit of 27,680 billion rupiah. This finding shows that changes in capital structure have a significant impact on corporate profits. The optimal capital structure can maximize the profit earned, because the use of an efficient combination of own and borrowed capital can increase the value of the company and prevent the company from financial difficulties. This research is expected to contribute to financial decision making in the company and become a reference for further research.